Deconstructing ethnography : towards a social methodology for ubiquitous computing and interactive systems design /: towards a social methodology for ubiquitous computing and interactive systems design. ([2015]) - Button, Graham, 1950-; Crabtree, Andy; Rouncefield, Mark; Tolmie, Peter
No abstract available